2015
DOI: 10.1152/physiol.00052.2014
|View full text |Cite
|
Sign up to set email alerts
|

Performance Enhancement: What Are the Physiological Limits?

Abstract: Our objective is to highlight some key physiological determinants of endurance exercise performance and to discuss how these can be further improved. V̇o2max remains remarkably stable throughout an athletic career. By contrast, exercise economy, lactate threshold, and critical power may be improved in world-class athletes by specific exercise training regimes and/or with more years of training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
68
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 106 publications
5
68
0
1
Order By: Relevance
“…The present finding provides some support for Westgarth-Taylor et al [37] who reported reduced [La -] at the same absolute work rate (80% peak power output) after HIIT and Weston et al [38] who showed an increased buffering capacity was Endurance performance in well-trained athletes is influenced by physiological factors including V O2max, lactate threshold/critical power, gross mechanical efficiency and genetic predispositions [360] . Since V O2max remains fairly stable across an athletic career, and therefore has minimal potential for further improvement once high-load endurance training has been undertaken for several years [360] , it is unlikely that changes in V O2max resulted over the course of ~3-4 weeks in the present study.…”
Section: Km Time Trialsupporting
confidence: 82%
See 1 more Smart Citation
“…The present finding provides some support for Westgarth-Taylor et al [37] who reported reduced [La -] at the same absolute work rate (80% peak power output) after HIIT and Weston et al [38] who showed an increased buffering capacity was Endurance performance in well-trained athletes is influenced by physiological factors including V O2max, lactate threshold/critical power, gross mechanical efficiency and genetic predispositions [360] . Since V O2max remains fairly stable across an athletic career, and therefore has minimal potential for further improvement once high-load endurance training has been undertaken for several years [360] , it is unlikely that changes in V O2max resulted over the course of ~3-4 weeks in the present study.…”
Section: Km Time Trialsupporting
confidence: 82%
“…Since V O2max remains fairly stable across an athletic career, and therefore has minimal potential for further improvement once high-load endurance training has been undertaken for several years [360] , it is unlikely that changes in V O2max resulted over the course of ~3-4 weeks in the present study.…”
Section: Km Time Trialmentioning
confidence: 88%
“…The positive association between physical activity and blood volume (BV) was established in the late 1940s by Swedish scientists demonstrating that exercise‐trained men and women had higher values than inactive peers (Kjellberg et al., ). This finding has been confirmed on numerous occasions with cross‐sectional study designs (Dill et al., ; Brotherhood et al., ; Heinicke et al., ; Lundby & Robach, ), which nevertheless are limited to ascertain whether the augmented BV determined in trained individuals is primarily attributed to exercise training (ExT) per se or associated with other differences between individuals (e.g, genetics). Yet, on the basis of longitudinal studies, ExT is generally accepted to prompt BV expansion, at least in healthy young individuals (Convertino, , ; Sawka et al., ).…”
mentioning
confidence: 79%
“…Large increases in RBCV with ExT are mainly advocated on the basis of cross‐sectional comparisons (Heinicke et al., ), notwithstanding the fact that ExT‐related mechanisms stimulating erythropoiesis are uncertain (Montero et al., ,b). In turn, longitudinal ExT studies (not including any type of hypoxic training) have reported conflicting RBCV responsiveness, ranging from unaltered (Shoemaker et al., ; Stachenfeld et al., ; Takeno et al., ; Okazaki et al., , ; Gass et al., ; Helgerud et al., ) to 10% increments (Bonne et al., ), which nonetheless remains well below the absolute values observed in some athletes (Lundby & Robach, ). The small sample size, distinct training characteristics, study population, and methodology of previous studies may have compounded the determined effect of ExT on RBCV (Bass et al., ; Fortney & Senay, ; Convertino et al., ; Ray et al., ; Green et al., ; Stevens et al., ; Carroll et al., ; Shoemaker et al., ; McCarthy et al., ; Pickering et al., ; Stachenfeld et al., ; Mtinangi & Hainsworth, ; Takeno et al., ; Okazaki et al., , ; Gass et al., ; Helgerud et al., ).…”
mentioning
confidence: 99%
“…Consequently, concerning training effects (Platonov, 1999; Noakes, 2000; Abbiss and Laursen, 2005), concepts integrating the prescription of both intensity and duration within one model are needed with respect to the main aims in endurance training which are to increase maximal oxygen uptake, the maximal sustainable speed, or power (threshold speed), and to increase economy and time to exhaustion (Lundby and Robach, 2015). …”
Section: Introductionmentioning
confidence: 99%